Optimizing Nephron Performance: The Old, the New, and the New–Old Diuretic Therapies - Flavio D. Fuchs; Guilherme S. Procianoy; Leonardo G. Bottino; Sandra C. Fuchs; Paul K. Whelton (Biomedicines)
Pharmacological influence on nephron function has modified the clinical course of hypertension, heart failure, and chronic kidney disease. (CKD). This is a review of the efficacy of old diuretics and the incremental efficacy of new diuretics in managing hypertension, heart failure, and CKD, concluding with new evidence on the effectiveness of old agents. The efficacy of “older” diuretic agents, such as thiazide and loop diuretics, on heart failure and CKD has been primarily explored in nonrandomized studies. However, the efficacy of these agents and indapamide, a slightly newer but still “old” diuretic in preventing blood pressure-related cardiovascular disease, has been demonstrated in randomized controlled trials. Potassium-sparing agents counteract some of the adverse effects of thiazides and have been shown to prevent cardiovascular events in patients with heart failure. Newer drugs with a diuretic effect, such as gliflozins, act through a new mechanism of action in the kidney and have shown efficacy in controlling symptoms and preventing cardiovascular events in patients with heart failure, regardless of diabetes. Furthermore, gliflozins have prevented the progression of chronic kidney disease in patients with and without diabetes mellitus. New evidence detailing the efficacy of old agents has emerged. Chlorthalidone had a large blood-pressure-lowering effect in patients with stage IV CKD. Acetazolamide was effective in accelerating the clinical control of patients with acute heart failure, including patients with some reduction in kidney function. We anticipate investigating the comparative impact of combining different agents to optimize nephron function in the future.